2018
DOI: 10.1002/ddr.21438
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interaction between docosahexaenoic acid and diclofenac on inflammation, nociception, and gastric security models in rats

Abstract: Preclinical Research & Development The addition of polyunsaturated fatty acids to nonsteroidal anti-inflammatory drugs can increase their antinociceptive activity and produce a gastroprotective effect. The aim of the present study was to examine the effects of the interaction between docosahexaenoic acid (DHA) and diclofenac on inflammation (fixed ratios 1:1, 1:3, and 3:1), nociception (fixed ratio 1:3), and gastric injury in rats. DHA, diclofenac, or combinations of DHA and diclofenac produced anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
5
1
Order By: Relevance
“…So, in our work, the interaction index for phase 1 is similar to the reported for xylopic and docosahexaenoic acid but lower than the interactions demonstrated by the other authors. Likewise, for phase 2, our index of 0.09 is 45% lower than the value reported for the smallest interaction index of 0.20 for docosahexaenoic acid by Miranda‐Lara et al, 2018. In this sense, the experimental dose reported for EUG + DFC is below those reported by other works.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…So, in our work, the interaction index for phase 1 is similar to the reported for xylopic and docosahexaenoic acid but lower than the interactions demonstrated by the other authors. Likewise, for phase 2, our index of 0.09 is 45% lower than the value reported for the smallest interaction index of 0.20 for docosahexaenoic acid by Miranda‐Lara et al, 2018. In this sense, the experimental dose reported for EUG + DFC is below those reported by other works.…”
Section: Discussioncontrasting
confidence: 82%
“…Thus, the degree of improved effect (synergism) reflects the value below 1 of this index, since it represents the quantitative marker for the combination of drugs and the metric of the measured effect (Tallarida, 2002). Other combinations of DFC, with natural components, have been described, such as curcumin with an interaction index of 0.51 (De Paz‐Campos, Ortiz, Piña, Zazueta‐Beltrán, & Castañeda‐Hernández, 2014), xylopic acid of 0.27 (Woode, Ameyaw, Abotsi, & Boakye‐Gyasi, 2015), Matricaria chamomilla of 0.42 (Ortiz et al, 2017), docosahexaenoic acid of 0.20 (Miranda‐Lara, Ortiz, Rodríguez‐Ramos, & Chávez‐Piña, 2018) and α‐bisabolol of 0.39 (Ortiz, Cariño‐Cortés, Ponce‐Monter, Castañeda‐Hernández, & Chávez‐Piña, 2018). So, in our work, the interaction index for phase 1 is similar to the reported for xylopic and docosahexaenoic acid but lower than the interactions demonstrated by the other authors.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite three decades of epidemiological, clinical, and experimental studies providing strong evidence of anticancer activity, the use of NSAIDs such as diclofenac for cancer chemoprevention is not recommended due to the potential risk of gastrointestinal, renal, and cardiovascular side effects [8,41,42]. Our current findings, together with the recent reports showing that the combination of NSAIDs with ω-3 PUFAs used for anti-inflammatory synergism offer protection against gastric damage induced by COX inhibitors [43,44], provide strong evidence of the benefit that could be accrued by combining the two compounds. Besides, such combination could lead to dose reduction of both agents, which could address their potential adverse effects when used alone at higher doses.…”
Section: Discussionsupporting
confidence: 56%
“…Docosahexaenoic acid (DHA, Figure 4), a type of O3FA, has been studied in combination with drugs such as diclofenac. Animal studies on this combination attributed synergistic interaction at a systemic level in terms of nociception, inflammation and gastric security [79]. A similar study found that DHA combined with naproxen affords supra-additive nociception and gastric safety [80].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 88%